Peluang pemanfaatan aplikasi dan media pembelajaran berbasis teknologi sebagai inovasi pembelajaran di era digital - Sofia Rahmawati; Elga Surya Andika; Mochamad Kamil Budiarto (Universitas Hamzanwadi, 2022)
Information and communication technology has the opportunity to be applied in the learning process, one of which is through the creation of digital learning media as a tool to support learning activities. This study aims to conceptually describe the opportunities for various applications to be applied in the learning process and become the basic material in the development of media and learning materials based on information and communication technology (ICT). This research method is a literature study which will contain various analyzes sourced from scientific journals, books and other supporting documents as data sources. The focus of the literature search which is the subject of research consists of several key words, such as learning media, ICT, learning applications and 21st century competencies. The results of the study succeeded in describing various ICT-based learning media formats accompanied by the benefits that users would receive from these media. ICT-based learning, both from the cognitive, affective and psychomotor aspects. In addition, this research also conveys the benefits and advantages of each application that can create a digital learning media to make it easier for educators to identify related opportunities for use that are tailored to the needs of each educational institution.